Asymptotic dynamics of a sixth-order integro-differential equation. Issue 15 (13th October 2022) - Chen, Bosheng; Liu, Changchun
Abstract : We consider a sixth-order integro-differential equation with periodic boundary conditions. The equation describes the phase transition dynamics in ternary oil–water–surfactant systems. Using the energy methods and the basic dissipative estimate, we establish the required estimates. Furthermore, based on these estimates, we prove the existence of the attractors by a decomposition of the solution semigroup.